2014
DOI: 10.1007/s13762-014-0500-8
|View full text |Cite
|
Sign up to set email alerts
|

Processing separated digestate by vermicomposting technology using earthworms of the genus Eisenia

Abstract: In the current study, pre-composting and subsequent vermicomposting of separated digestate (also called separated biogas plant slurry) were verified to improve its properties for use as a soil conditioner. Increasing the proportion of straw in combination with separated digestate had a positive effect on reducing both weight and volume during vermicomposting. The pH value decreased and was found to be between 7.3 and 7.7 in the final vermicomposts. Due to a loss in organic matter, the total content of macro-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 24 publications
1
25
0
3
Order By: Relevance
“…This is in accordance with the results of (Atiyeh et al 2000; Venkatesh and Eevera 2008; Raphael and Velmourougane 2011). pH decrease may be due to the nitrification process experienced by the composting process, accumulation and reduction of organic acids from microbial metabolism, production of fulvic and humic acids during decomposition or as a result of NH3 volatilization during composting process (Albanell et al 1988; Hanc and Vasak 2015; Cáceres et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the results of (Atiyeh et al 2000; Venkatesh and Eevera 2008; Raphael and Velmourougane 2011). pH decrease may be due to the nitrification process experienced by the composting process, accumulation and reduction of organic acids from microbial metabolism, production of fulvic and humic acids during decomposition or as a result of NH3 volatilization during composting process (Albanell et al 1988; Hanc and Vasak 2015; Cáceres et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Research experiences at lab-, pilot-and full-scale have been reported for technologies such as (i) precipitation / crystallization of magnesium and calcium phosphates, (ii) pressure-driven membrane filtration involving microfiltration, ultrafiltration, nanofiltration and/or reverse osmosis, (iii) NH 3 stripping followed by absorption under acidic conditions, (iv) adsorption and ion exchange, and (v) thermal treatment, among others. Biological methods have also been assessed; this includes, among others, (vermi)composting treatments applied to solid material fractions (Hanc and Vasak, 2015;Magrí and Teira-Esmatges, 2015;Zeng et al, 2016) and algae cultivation techniques applied to liquid streams (Cai et al, 2013;Monlau et al, 2015). Composting as post-treatment of the digestate forces the aerobic biodegradation of remaining organic matter, favoring the stability and maturity of the final product.…”
Section: 65mentioning
confidence: 99%
“…Unlike normal composting process, vermicomposting process involves both earthworms and microorganisms to biodegrade organic solid waste (Sim and Wu, 2010;Wu et al, 2014). Microorganisms are responsible for the biochemical degradation of organic matter whilst the earthworms help promote aeration conditions, fragment the substrate and subsequently increase the microbial activity (Hanc and Vasak, 2015).…”
Section: Introductionmentioning
confidence: 99%